Influence of composition of cathodic deposition electrolyte on morphology and capacity properties of MnO2 film - Chernyavina, Valentina Vladimirovna; Dyshlovaya, Yaroslava Aleksandrovna; Berezhnaya, Aleksandra Grigor'evna (Электрохимическая энергетика, 2025)
Manganese oxide was obtained by cathodic electrochemical deposition from the electrolyte solutions adding sodium nitrate or sulfate. The structural characteristics and the elemental composition of the MnO2 samples were studied by energy dispersive microanalysis, IR spectroscopy, and transmission electron microscopy. The electrochemical characteristics of the electrodes were determined by cyclic voltammetry, galvanostatic charge-discharge and impedance spectroscopy in 0.5M Na2SO4 solution. The dependence of the structural and capacitive properties of the MnO2 electrodes on the anion nature in the electrolyte for electrochemical deposition was determined. High capacitance characteristics were obtained for the MnO2 sample deposited from the electrolyte adding sodium sulfate. Its specific capacity was 215 F/g at the scanning speed of 5 mV/s.